Analys of Factors Associated with Exponencial Growth of Daily COVID-19 Cases During Colombia First Epidemiological Wave (2021)
The exponential growth of daily infections by Covid-19 has been one of the characteristics that most affects the dynamics of the Covid-19 pandemic. In this sense, the most significant economic and health impacts have occurred during periods of exponential growth. This work focuses on estimating these periods during the first epidemiological wave, and analyze their associated factors, using deterministic and statistical methods. The existence of 10 periods of exponential growth, of which the smallest period has a range of 4 days, while the biggest has a range of 37 days. The highest and lowest infection rates were k1 = 0,5535 and k10 = 0,0521, respectively, with ranges of 4 days. Failure to comply with prevention and containment mea- sures on key dates such as Holy Week, Mother’s Day, the day without value added tax (IVA for its acronym in spanish) and holidays have been the factors that most influence exponential growth; in addition, the reopening of economic sectors and the increase in testing in June con- tributed to the detection of cases, and therefore two periods of exponential growth.